Dissociation Rate Constants of Human Fibronectin Binding to Fibronectin-binding Proteins on Living Staphylococcus aureus Isolated from Clinical Patients - Casillas-Ituarte, Nadia N. (American Society for Biochemistry and Molecular Biology, 2012)
Staphylococcus aureus is part of the indigenous microbiota of humans. Sometimes, S. aureus bacteria enter the bloodstream, where they form infections on implanted cardiovascular devices. A critical, first step in such infections is a bond that forms between fibronectin-binding protein (FnBP) on S. aureus and host proteins, such as fibronectin (Fn), that coat the surface of implants in vivo. In this study, native FnBPs on living S. aureus were shown to form a mechanically strong conformational structure with Fn by atomic force microscopy. The tensile acuity of this bond was probed for 46 bloodstream isolates, each from a patient with a cardiovascular implant. By analyzing the force spectra with the worm-like chain model, we determined that the binding events were consistent with a multivalent, cluster bond consisting of ∼10 or ∼80 proteins in parallel. The dissociation rate constant (k(off), s(−1)) of each multibond complex was determined by measuring strength as a function of the loading rate, normalized by the number of bonds. The bond lifetime (1/k(off)) was two times longer for bloodstream isolates from patients with an infected device (1.79 or 69.47 s for the 10- or 80-bond clusters, respectively; n = 26 isolates) relative to those from patients with an uninfected device (0.96 or 34.02 s; n = 20 isolates). This distinction could not be explained by different amounts of FnBP, as confirmed by Western blots. Rather, amino acid polymorphisms within the Fn-binding repeats of FnBPA explain, at least partially, the statistically (p < 0.05) longer bond lifetime for isolates associated with an infected cardiovascular device.